2022
DOI: 10.1155/2022/1781415
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation Study of Progressive Collapse of Reinforced Concrete Frames with Masonry Infill Walls under Blast Loading

Abstract: The influence of masonry infill walls on the progressive collapse performance of reinforced concrete (RC) frame structures was investigated in this paper, using a nonlinear dynamic analysis approach. Based on ANSYS/LS-DYNA finite element software, two finite element models of RC frame structures with and without masonry infilled walls were established. Then, the collapse modes of the two RC frame structure models were analyzed for different scaled distance blast loads, different locations of column damage, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…As scholars have done more comparative experiments on bearing capacities under various loading rates, the work counted dynamic increase factor (DIF) for bearing capacities of RC structural members with variations in strain rates, as shown in Figure 7. Data were taken from [5,8,10,11,14,15,17,19,23,45,47,49,51,52,55,56,64,65,67,74,129]. Due to the non-negligible dynamic effects on the mechanical behaviors of RC structural members, RC structural members exhibit different mechanical properties under static and dynamic loading (i.e., maximum bearing capacity, stiffness, ductility factor and hysteretic behavior).…”
Section: Dynamic Modified Model At Member Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…As scholars have done more comparative experiments on bearing capacities under various loading rates, the work counted dynamic increase factor (DIF) for bearing capacities of RC structural members with variations in strain rates, as shown in Figure 7. Data were taken from [5,8,10,11,14,15,17,19,23,45,47,49,51,52,55,56,64,65,67,74,129]. Due to the non-negligible dynamic effects on the mechanical behaviors of RC structural members, RC structural members exhibit different mechanical properties under static and dynamic loading (i.e., maximum bearing capacity, stiffness, ductility factor and hysteretic behavior).…”
Section: Dynamic Modified Model At Member Levelmentioning
confidence: 99%
“…As scholars have done more comparative experiments on bearing capacities under various loading rates, the work counted dynamic increase factor (DIF) for bearing capacities of RC structural members with variations in strain rates, as shown in Figure 7. Data were taken from [5,8,10,11,14,15,17,19,23,45,47,49,51,52,55,56,64,65,67,74,129].…”
Section: Dynamic Modified Model At Member Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…The consistent research findings are concluded that as the loading rate increases, both the tensile strength and compressive strength of concrete, the yield strength and ultimate strength of reinforcement are magnified, and the elastic modulus and the strain corresponding to the compressive strength of concrete are also affected by the loading rate [2]. As for structural members consisting of RC materials, such as columns [3][4][5][6], beams [7][8][9][10][11][12][13][14], shear walls [15][16][17][18][19] and joints [20][21][22][23][24][25], changes in mechanical behaviors to different degrees are observed for specimens under various loading rates, namely the dynamic effect at the member level. Different failure patterns of RC structural members could be observed in seismic hazards, as shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical methods such as the finite element analysis (FEA) and finite difference method (FDM) have been extensively used to analyze the behavior of such structures. FEA is a powerful numerical tool that is widely utilized in structural engineering to investigate the behavior of structures subjected to various loading conditions [1]. The MDOF frames are a type of structural system that is commonly employed in modern buildings and bridges.…”
Section: Introductionmentioning
confidence: 99%